Tingkat Prokrastinasi Akademik Berdasarkan Intensitas Penggunaan Media Sosial di SMP Negeri 18 Palembang - Junia, Ayunda Vini; Sofah, Rahmi; Putri, Rani Mega (Jurnal Konseling Komprehensif: Kajian Teori dan Praktik Bimbingan dan Konseling, 2019)
This study aims to describe the level of academic procrastination based on the intensity of the use of social media in Palembang State Middle School 18. The population consisted of 120 students from class VIII with sample selection using a purposive sampling technique so that getting samples for each category in the form of: Light Users (numbered users) totaling 41 students, Medium Users (medium users) totaling 37 students, and Heavy Users 42 students. Research uses a quantitative approach with survey methods. The data collection technique used a closed questionnaire to measure the intensity of social media use as well as sample determination and the Likert scale to measure the tendency of academic procrastination. The data analysis technique used is descriptive quantitative. The results showed that the majority of subjects in the Light Users category were low on academic procrastination with a percentage of 53.7%, the Medium Users category including being on academic procrastination with a percentage of 43.2% and the Heavy Users category including academic procrastination with 45.3% . The results showed that the more often students used social media, the higher the tendency to do academic procrastination.